Morphological profiles of fatigue in Sarcoidosis patients. (30th September 2021) - Schnellbächer, Gereon Johannes; Kettenbach, Sarah; Löffler, Leonie; Dreher, Michael; Habel, Ute; Votinov, Mikhail
Highlights: Fatigue in sarcoidosis patients correlates with morphological alterations. Alterations mainly focus on structures associated with decision-making and emotional regulation as well as perception. There is a broad overlap of structural alterations between depressive and fatigue symptomatology in sarcoidosis patients. Fatigue seems to be a heterogeneous disease with varying patterns of structural alterations. Abstract: Introduction: Sarcoidosis is a chronic inflammatory disease often associated with chronic fatigue. Prevalence of fatigue can be measured via neuropsychological testing. Its pathophysiology is insufficiently understood. Structural analysis might help with the development of novel treatment methods. Methods: We recruited 30 sarcoidosis patients whose fatigue severity and depressive symptom presence was measured through validated neuropsychological self-assessment. T1-weighted structural images were acquired and VBM preprocessing was conducted. Total scores of these tests and subscales were correlated through multiple regression analysis to the brain morphometry. Results: Fatigue severity positively correlated with gray matter volumes in the striatum, the cingulate cortex and the cerebellum and negatively in the parietal and temporal lobe and posterior insula. Subscale analysis indicated a correlation between cognitive fatigue and striatum involvement as well as between physical and psychosocial fatigue and cerebellar alterations. Discussion: Structural analysis delineated two structural patterns associated with the presence of fatigue. One such pattern mainly seemed to involve structures with a focus on decision-making processes while the other indicated alterations in regions vital for perception. Fatigue seems to be a heterogeneous disease, where varying dimensions of reported symptoms correlate with different patterns of structural changes.